Simulasi Docking Senyawa Napthoquinones Umbi Bawang Tiwai (Eleutherine americana Merr.) terhadap Bakteri Mycobacterium tuberculosis: Docking Simulation of Umbi Bawang Tiwai Napthoquinones Compound (Eleutherine americana Merr.) against Mycobacterium tuberculosis bacteria - Irmayanti Irwan; Hajrah Hajrah; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Bawang tiwai (Eleutherine americana Mirr.) is a plant empirically used as an antituberculosis. This plant is thought to have potential because having a compound naphthoquinone potential antituberculosis seen from the average value of the MIC between 206,6 and 12.5 ?M. This study aims to examine a model of the interaction of compounds derived naphthoquinone of bawang tiwai against the side of the fastener from the bacterium Mycobacterium tuberculosis. The method used is docking molecular using AutoDock tools, and Biovia 2020, the prediction of physicochemical which refers to the law of the five Lipinski of using pkCSM online tool. The receptor proteins used were InhA (PDB: 2X23) and the test ligands of elecanacin, eleutherin, eleutherol, and isoeleutherin. The results show that the four compounds comply with Lipinski's five laws, and the docking analysis data is the value of free bond energy (?G) of the four compounds, respectively, -5.82, -4.80, - 5.06, -5.52. The ?G value is below the natural ligand, namely -8, 19, and no hydrogen bonding interaction. It can be concluded that the four naphthoquinone derivative compounds in bawang tiwai lack the potential to bind to the binding site of the Mycobacterium tuberculosis bacteria.